Critical Analysis on the Thoughts of Ibn Jarir al-Tabari about Jilbab in the Quran Surah al-Aḥzab Verse 59 - Rohmansyah Rohmansyah (Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
When viewed from the aspect of the definition of the jilbāb (long, loose-fit outer garment worn by some Muslim women), the issue of jilbāb is a social-religious problem that is often used as a material for discussion among experts of fiqh (Islamic jurisprudence) and tafsir (exegesis, interpretation), both classic and contemporary. This research focuses on the interpretation of the jilbāb in the Quran Surah al-Aḥzab verse 59 based on the view of al-Tabari. The researcher conducts a critical study of his thoughts by using the library research method and the sociological-historical approach. The findings proved that al-Tabari was a very careful person in interpreting the Quran based on the hadith (the record of the words, actions, and the silent approval of the Islamic prophet Muhammad) and the atsar (the words or actions) of the sahabah (the companions of the prophet). The jilbāb, according to him, was something that covered the head, face, and one of the eyes (the left one). Such interpretation of al-Tabari certainly cannot be separated from the aspects of socio-historical phenomena that occurred in the past where the Abbasid Caliphate’s seizure of territory took place to have implications for human freedom, especially for women. Such a condition of insecurity for a woman that made al-Ṭabari interpreted jilbāb as such in order to protect women. However, if the definition of jilbāb is contextualized today, then it is no longer relevant because the conditions are safe, and women are free to fulfill their needs. Still, a woman must maintain her honor and cover her aurat (intimate parts in Islam), except for something that can be seen which are the palm of the hands, and the face.